News Coverage On Anti-Islam Film "Fitna": An Analysis Of U.S And U.K Mainstream Newspapers - Mohd Faizal Kasmani; Noor Adzrah Ramle; Suria Hani A. Rahman (Universiti Sains Islam Malaysia, 2024)
On the 27' of March 2008, a 15-minute Dutch film, "Fitna", was released on the Internet. The film, which shows images of Quranic verses with clips of violence, received harsh condemnation from the Muslims all over the world. This event further cemented the issue of misconception of Western media towards Islam where Muslims have been repeatedly portrayed in hostile manner. This study will examine the coverage of major newspapers in the US and UK before and after the release of the anti-Islam film. The aim of the research is to look at how Western media frame the news pertaining to the release of the film which is seen by Muslim society as a deliberate and blatant attack towards Islam. There were 64 articles analysed from five newspapers in the US and five from the UK. Four indicators will be used in the content analysis of the articles; the framing of articles, what trigger the news, the underlying messages and the choice of sources. The results do not support the expectation that Western media are bias towards the filmmaker's right to release his anti-Islam film. Majority of the articles also sided with religious sensitivity of Muslim communities.